Peningkatan Pengetahuan Siswa melalui Edukasi Bahaya Penggunaan Gadget Berlebihan di SDN 3 Belor Kabupaten Grobogan - Fitriani Fitriani; Anita Lufianti; Yesita Ragil K; Rahmawati Rahmawati; Mika Agustiana; Christina Nur W; Indah Sari; Afid Triya Arina Sofi Yanur; Wiwin Danika Rismawati; Salisa Hidayatul Maula; Intan Nur Aliyah; Diah Ayu Istikhomah (LPPM STIKes Muhammadiyah Ciamis, 2025)
Introduction:In helping prevent excessive use of gadgets, the Real Work Lecture of An-Nuur Purwodadi University group 6 chose a work program that aims to provide knowledge of the use of appropriate technology to children to build a good mindset in line with the development of technology and communication, especially in the field of education. Gadgets are technological developments that have their own attractions, have become friends, are known to be more often used as children's games and even toddlers are familiar with gadgets, so if they are not restricted, they can pose a dangerous risk to their users. Objective:The purpose of this activity is to increase the knowledge of students of SD N 3 Belor about the wise and safe use of gadgets so that they can be adjusted to their functions. This activity began by providing Health Education about gadgets which includes the benefits, dangers and how often to use gadgets in daily life. Method: Then, it was continued with the provision of material continued with the provision of material by lecture methods, animated videos and questions and answers. Result : The outreach/socialization program, conducted through lectures and discussions about the dangers of gadget use, was attended by all students, many of whom reported excessive use of their devices for YouTube, games, and other activities. Students expressed interest in participating, stating they understood the dangers of gadgets and were willing to limit their use. Conclusion : The gadget-related education program at SD N 3 Belor aims to educate students about the dangers of gadgets. This helps them avoid the negative impacts of technology and become wise citizens of the nation.